Land use and land cover dynamics in the dehesa of Sierra Morena Biosphere Reserve (Sierra Norte de Sevilla Natural Park, Spain), 1956-2007 - Mancilla Leytón, Juan Manuel; Puerto Marchena, Antonio; Martín Vicente, Ángel (Instituto de Ecología, A.C., 2017)
The dehesa, a representative savanna-like ecosystem type, has played and plays an important economic, ecological and social role, in addition to the valuable environmental services that it provides. The present study is focused on the analysis of the changes in the land use /cover of the dehesa in the Sierra Norte de Sevilla Natural Park (Sierra Morena Biosphere Reserve) during the last 50 years. In order to estimate the consequences that the change of land uses and, the activities that are carried out on it have on the dynamics of the dehesa, a diachronic analysis was performed for the period 1956-2007 using the digital geographic information available. The most important changes observed were related to: i) the increase of urban areas, water surface area, reforestation areas, eroded areas, mining areas and dumping sites; and ii) the decrease of cultivation areas, dehesa, scrubland and pastureland. The changing dynamics did not strictly respond only to phytosociological aspects, but it is necessary to explain the evolution of the landscape from the complex balance between biophysical and socioeconomic dynamics, where the current environmental changes also make it very difficult to ensure the persistence of this ecosystem. The present legislation promotes the development of a clear and up-to-date diagnosis of the problems that this ecosystem is facing. In this sense, the geographic information systems may be very useful at establishing the guidelines for the conservation and regeneration of the dehesas, and at spreading their environmental values.